Packaging bag

The packaging bag design addresses the issue of reduced openability and bursting in microwave-heated bags by incorporating a steam draining section and an open-circuit induced processing section, ensuring effective steam release and easy opening post-heating.

JP2025054951APending Publication Date: 2025-04-08TOPPAN HOLDINGS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023164208
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Microwave-heated packaging bags face challenges with reduced openability due to heat-softening of the film, while also needing to prevent bursting during heating.

Method used

A packaging bag design featuring a steam draining section and an open-circuit induced processing section, both formed to satisfy specific conditions based on maximum 5% stretch strength, allowing for easy opening after microwave heating while preventing bursting.

Benefits of technology

The solution ensures good openability of the packaging bag after microwave heating while maintaining integrity to prevent bursting, by selectively ejecting steam and utilizing the open induction processing section effectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054951000001_ABST
    Figure 2025054951000001_ABST
Patent Text Reader

Abstract

To provide a packaging bag which can secure satisfactory openability after microwave heating while preventing rupture upon microwave heating.SOLUTION: A packaging bag according to an embodiment is the one for microwave heating which is sealed to form a storage space for storing contents. The packaging bag comprises: a film having a sealant layer and an external layer; and a steam release processing part and an opening induction processing part formed at the external layer. The steam release processing part and the opening induction processing part are formed so as to satisfy a condition 1 and a condition 2: (condition 1) where the 5% drawing maximum strength of a first test piece with the steam release processing part is below 75% relative to the 5% drawing maximum strength of a standard test piece without the steam release processing part and the opening induction processing part, and (condition 2) where the 5% drawing maximum strength of a second test piece with the opening induction processing part is 80% or more relative the 5% drawing maximum strength of the standard test piece.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a packaging bag. [Background technology]

[0002] There is an increasing need for food packaging that can be heated in a microwave oven before eating. From the viewpoint of convenience for consumers, packaging bags that can be heated directly in a microwave oven (see, for example, Patent Document 1) are known. Packaging bags that are heated in a microwave oven in this way are configured to automatically release internal pressure to the outside of the packaging bag when the internal pressure reaches a certain pressure, in order to prevent the packaging bag from bursting due to expansion caused by an increase in internal pressure due to microwave heating. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2014-227222 Summary of the Invention [Problem to be solved by the invention]

[0004] When a packaging bag is heated in a microwave oven, the film that constitutes the packaging bag is thermally softened. When the film is thermally softened in this way, it becomes difficult to cut. As a result, the ease of opening the packaging bag decreases.

[0005] An object of one aspect of the present invention is to provide a packaging bag that can be prevented from bursting when heated in a microwave oven while ensuring good openability after heating in a microwave oven. [Means for solving the problem]

[0006] [1] A packaging bag according to one aspect of the present invention is a packaging bag for microwave heating that is sealed to form a storage space for storing contents, comprising: a film having a sealant layer and an outer layer laminated to the sealant layer; a steam release processed part formed on the outer layer for venting steam generated in the storage space by heating; and an opening induction processed part formed on the outer layer for assisting opening, wherein the steam release processed part and the opening induction processed part are formed so as to satisfy Condition 1 and Condition 2 based on the maximum strength at 5% elongation defined below. [Maximum strength at 5% stretching] A rectangular test piece 15 mm wide is prepared, and held in the long side direction by a pair of holders. In an environment of 100°C±5°C, the distance between the pair of holders is 100mm±2mm, and the test piece is pulled in the long side direction at a tensile speed of 200mm / min. The maximum strength is when the test piece is displaced by 5% or when it breaks within 5% displacement. (Condition 1) When the test piece has the same layer structure as the film, the direction perpendicular to the long side direction is the MD direction of the film, and the steam release processed portion and the opening induction processed portion are not formed, and when the test piece in which the steam release processed portion is formed in the center of the pair of retaining portions in the long side direction of the reference test piece along the direction perpendicular to the long side direction is called a first test piece, the 5% stretch maximum strength of the first test piece is less than 75% of the 5% stretch maximum strength of the reference test piece. (Condition 2) When the test piece in which the opening induction processing portion is formed in the center of the pair of retaining portions in the long side direction of the reference test piece along a direction perpendicular to the long side direction is referred to as a second test piece, the 5% elongation maximum strength of the second test piece is 80% or more of the 5% elongation maximum strength of the reference test piece.

[0007] In the above packaging bag, the steam release processed part is formed to satisfy condition 1, and the opening induction processed part is configured to satisfy condition 2. Therefore, even if the packaging bag has both a steam release processed part and an opening induction processed part, the packaging bag can be easily opened after microwave heating by using the opening induction processed part while selectively releasing steam from the steam release processed part during microwave heating. In other words, the above packaging bag can ensure good openability after microwave heating while preventing rupture during microwave heating.

[0008] [2] In the packaging bag described in [1] above, the sealant layer may be made of linear low-density polyethylene.

[0009] [3] In the packaging bag according to [1] or [2] above, the internal pressure of the storage space may be 0.113 MPa or less when heated at 500 W for 2 minutes.

[0010] [4] The packaging bag according to any one of [1] to [3] above may include a tubular portion made of the film and having a back seal portion, a first seal portion formed at a first end of the tubular portion, and a second seal portion formed at a second end opposite to the first end of the tubular portion. Such a packaging bag is a pillow-shaped packaging bag.

[0011] [5] In the packaging bag described in any one of [1] to [4] above, the outer layer has a first resin layer and a second resin layer located between the first resin layer and the sealant layer, the steam release processed portion is a scratch processed portion penetrating the first resin layer and the second resin layer, and the opening induction processed portion is a scratch processed portion penetrating one of the first resin layer and the second resin layer, or may be a scratch processed portion formed from the first resin layer to partway through the second resin layer.

[0012] In the configuration described in [5] above, the steam release processed portion is likely to satisfy condition 1, and the opening induction processed portion is likely to satisfy condition 2.

[0013] [6] In the packaging bag described in any one of [1] to [4] above, the outer layer may be a first resin layer, the steam release processed portion may be a scratch processed portion penetrating the first resin layer, and the opening induction processed portion may be a scratch processed portion formed in the first resin layer so as not to penetrate the first resin layer.

[0014] In the configuration described in [6] above, the steam release processed portion is likely to satisfy condition 1, and the opening induction processed portion is likely to satisfy condition 2. Effect of the Invention

[0015] According to the present invention, it is possible to provide a packaging bag that can be prevented from bursting when heated in a microwave oven while ensuring good openability after heating in a microwave oven. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a front view showing a schematic diagram of a packaging bag according to the present embodiment. [Diagram 2] FIG. 2 is a rear view of the packaging bag shown in FIG. [Diagram 3] FIG. 3 is a schematic cross-sectional view taken along line III-III in FIG. [Figure 4] FIG. 4 is a schematic diagram for explaining an example of a layer structure of a film of the packaging bag shown in FIG. [Diagram 5] FIG. 5 is a plan view of a test piece for measuring the maximum strength at 5% elongation. [Figure 6] FIG. 6 is a plan view of a test piece for measuring the maximum strength at 5% elongation of a scratched portion of a film. [Figure 7] FIG. 7 is a schematic diagram of a first example of forming a scratched portion. [Figure 8] FIG. 8 is a schematic diagram of a second example of forming the scratched portion. [Figure 9] FIG. 9 is a schematic diagram of a third example of forming the scratched portion. [Figure 10] FIG. 10 is a schematic diagram of a fourth example of forming the scratched portion. [Figure 11]FIG. 11 is a schematic diagram of a fifth example of the formation of the scratched portion. [Figure 12] FIG. 12 is a schematic diagram of a sixth example of the formation of the scratched portion. [Figure 13] FIG. 13 is a diagram for explaining the packaging bags used in Experimental Examples 1 to 6. As shown in FIG. [Figure 14] FIG. 14 is a diagram showing the layer structures of the films used in Experimental Examples 1 to 6. [Figure 15] FIG. 15 is a table showing the experimental results of Experimental Examples 1 to 6. [Figure 16] FIG. 16 is a diagram showing the strength of the processing type of the scratch processing part, which is determined by the combination of the layer structure and the scratch processing part. [Figure 17] FIG. 17 is a chart in which the maximum internal pressure measurements shown in FIG. 15 correspond to the "strong processing" and "weak processing" shown in FIG. [Figure 18] FIG. 18 is a diagram for explaining the packaging bags used in Experimental Examples 7 to 12. As shown in FIG. [Figure 19] FIG. 19 is a table showing the experimental results of Experimental Examples 7 to 12. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. The same elements are given the same reference numerals, and duplicated explanations will be omitted. The dimensional ratios of the drawings do not necessarily match those in the description.

[0018] Fig. 1 is a front view showing a schematic diagram of a packaging bag according to the present embodiment. Fig. 2 is a rear view of the packaging bag shown in Fig. 1. Fig. 3 is a schematic diagram of a cross section taken along line III-III in Fig. 1. In the following description, the x-axis, y-axis, and z-axis shown in Figs. 1 to 3 may be used. The x-axis, y-axis, and z-axis are mutually perpendicular.

[0019] The packaging bag 1 is a pillow-shaped packaging bag for microwave heating that contains the contents 100. The contents 100 are food items that can be heated in a microwave oven. In this embodiment, the packaging bag 1 is a primary food packaging material intended to be placed, for example, directly in a microwave oven to heat the contents 100 in the microwave oven.

[0020] The packaging bag 1 has a tubular portion 2 made of a rectangular film 10, a first sealed portion 3 that seals a first end (opening end) 2a of the tubular portion 2, and a second sealed portion 4 that seals a second end (opening end) 2b of the tubular portion 2. The second end 2b of the tubular portion 2 is located opposite to the first end 2a of the tubular portion 2 in the direction of the central axis of the tubular portion 2.

[0021] The direction of the central axis of the tubular portion 2 is the x-axis direction. The direction perpendicular to the central axis is the y-axis direction. In the packaging bag 1, the x-axis direction corresponds to the MD direction (Machine Direction) of the film 10, and the y-axis direction corresponds to the TD direction (Transverse Direction) of the film 10.

[0022] As shown in Figs. 2 and 3, the tubular part 2 has a back seal part 5. In this embodiment, the surface of the packaging bag 1 on which the back seal part 5 is formed is the "back" of the packaging bag 1, and the surface opposite to the back seal part 14 is the "front" of the packaging bag 1. The back of the packaging bag 1 is the surface that is located on the table (tray) side in the microwave oven when the packaging bag 1 is placed in a microwave oven. The back seal part 5 is formed by heat sealing the inner surfaces of both side ends of the film 10 together. In Fig. 3, the back seal part 5 is shown in a state where it protrudes outward (or stands up against the back) in order to explain the position of the back seal part 5. Fig. 2 is a schematic diagram of the back seal part 5 shown in Fig. 3 in a state where it is laid down toward the back of the packaging bag 1.

[0023] In this embodiment, the back seal part 5 is located at the center of the packaging bag 1 in the y-axis direction. "The back seal part 5 is located at the center of the packaging bag 1 in the y-axis direction" means that the innermost end of the back seal part 5 (the end closest to the contents 100) is located at the center. The back seal part 5 extends from the first seal part 3 to the second seal part 4.

[0024] The packaging bag 1 is sealed by a first sealed portion 3, a second sealed portion 4 and a back sealed portion 5, and a storage space 6 for storing contents 100 is formed.

[0025] An example of the length of the packaging bag 1 in the x-axis direction is 120 mm or more and 300 mm or less. An example of the length of the packaging bag 1 in the y-axis direction is 100 mm or more and 250 mm or less. An example of the length between the first sealed portion 3 and the second sealed portion 4 of the packaging bag 1 is 90 mm or more and 290 mm or less. The length between the first sealed portion 3 and the second sealed portion 4 of the packaging bag 1 corresponds to the length of the storage space 6 in the x-axis direction. The width of the first sealed portion 3 and the second sealed portion 4 (an example of the length in the x-axis direction) is 5 mm or more and 15 mm or less. An example of the width of the back seal portion 5 is 5 mm or more and 15 mm or less. The width of the back seal portion 5 may be the length in the y-axis direction when the back seal portion 5 is folded toward the back as shown in FIG. 2.

[0026] Next, an example of the layer structure of the film 10 will be described with reference to Fig. 4. Fig. 4 is a schematic diagram for explaining an example of the layer structure of the film 10.

[0027] The film 10 is a laminated film having a sealant layer 11 and an outer layer 12. The thickness of the film 10 is, for example, 52 μm or more and 65 μm or less.

[0028] The sealant layer 11 is an inner layer of the film 10. The sealant layer 11 may be made of linear low density polyethylene (LLDPE). An example of the thickness of the sealant layer 11 is 36 μm or more and 66 μm or less.

[0029] The outer layer 12 is laminated on the sealant layer 11. The outer layer 12 is bonded to the sealant layer 11 by an adhesive layer 13. The adhesive layer 13 is made of an adhesive used in this technical field. The adhesive that makes up the adhesive layer 13 is, for example, a urethane-based adhesive.

[0030] The outer layer 12 has at least one resin layer. The outer layer 12 has at least a first resin layer 121. Examples of materials for the first resin layer 121 include polyethylene terephthalate (PET), nylon (or polyamide), polybutylene terephthalate (PBT), and the like. The first resin layer 121 may be a uniaxially or biaxially stretched film. For example, the first resin layer 121 may be a biaxially stretched PET film or a biaxially stretched nylon film (hereinafter sometimes referred to as an "ONY film"). An example of the thickness of the first resin film 12a is 12 μm or more and 25 μm or less.

[0031] The outer layer 12 may have a second resin layer 122, as illustrated in FIG. 4. Examples of materials for the second resin layer 122 include PET, nylon, and the like. The second resin layer 122 may be a uniaxially or biaxially stretched film. For example, the second resin layer 122 may be a biaxially stretched PET film. An example of the thickness of the second resin layer 122 is 12 μm or more and 16 μm or less. The first resin layer 121 and the second resin layer 122 may be bonded by an adhesive layer 13.

[0032] The outer layer 12 may have three or more resin layers. Again, adjacent resin layers may be joined by adhesive layers 13.

[0033] The laminate strength between adjacent layers among the multiple layers constituting the film 10 is, for example, 1 N / 15 mm or more in a 100° C. environment.

[0034] As shown in FIG. 1, the packaging bag 1 has a steam release processed portion 31 and an opening induction processed portion 32.

[0035] The steam release processed section 31 has a function of discharging excess steam from within the packaging bag 1 when the packaging bag 1 is heated in a microwave oven. The steam release processed section 31 is a section that, when the internal pressure of the packaging bag 1 exceeds a predetermined pressure during microwave heating, communicates with the storage space 6 and the outside of the packaging bag 1 to discharge steam from within the packaging bag 1 to the outside. The steam release processed section 31 is configured such that, when the pressure within the packaging bag 1 exceeds the above-mentioned predetermined pressure, the steam release processed section 31 selectively breaks to form a steam port. An example of the above-mentioned predetermined pressure is 0.113 MPa. In this case, for example, when the packaging bag 1 is heated in a microwave oven for 2 minutes at 500 W, the internal pressure of the storage space 6 can be maintained at 0.113 MPa or less. The internal pressure of the storage space 6 is atmospheric pressure (specifically, 0.995 MPa) or more.

[0036] The steam release processed portion 31 is formed substantially along the x-axis direction (MD direction) on the front surface of the packaging bag 1. The steam release processed portion 31 may be inclined by about ±2° with respect to the x-axis direction.

[0037] The opening induction processed portion 32 has a function of assisting in opening the packaging bag 1. The opening induction processed portion 32 is formed substantially along the x-axis direction (MD direction). The opening induction processed portion 32 may be inclined by about ±2° with respect to the x-axis direction. The opening induction processed portion 32 is formed on the front and back of the packaging bag 1. When viewed from the front (or back), the positions of the opening induction processed portions 32 formed on the front and back are the same.

[0038] The steam release processed portion 31 and the opening induction processed portion 32 are formed in the outer layer 12. Specifically, the steam release processed portion 31 and the opening induction processed portion 32 are formed in at least one resin layer that the outer layer 12 has.

[0039] The steam release processed portion 31 and the opening induction processed portion 32 are scratched portions. Therefore, in the following description, the steam release processed portion 31 and the opening induction processed portion 32 may be referred to as the scratched portion 30.

[0040] The steam release processed portion 31 is formed so as to satisfy condition 1 based on the "maximum strength at 5% stretch" and "ratio to the unprocessed portion" defined below, and the opening induction processed portion 32 is formed so as to satisfy condition 2 based on the above-mentioned maximum strength at 5% stretch.

[0041] [Maximum strength at 5% stretching] As shown in Fig. 5, a rectangular test piece 40 made of film F is prepared. The short side direction of the test piece 40 is the MD direction of film F. The length of the long side direction of the test piece 40 is 140 mm or more. The length of the short side direction of the test piece 40 is 15 mm.

[0042] The test piece 40 is held by a pair of chucks (holding parts) arranged along the long side direction of the test piece 40. In Fig. 5, the hatched parts indicate the areas of the test piece 40 that are held by the chucks. The distance between the pair of chucks (the distance between the pair of dashed lines in Fig. 5) is 100 mm ± 2 mm.

[0043] A tensile test is conducted in which the test piece 40 held by a pair of chucks is pulled in the long side direction. The tensile test is conducted in an environment of 100°C ± 5°C. The tensile speed in the tensile test is 200 mm / min. In the above tensile test, the maximum strength when the test piece 40 is displaced by 5% or when the test piece 40 breaks within 5% displacement is defined as the "5% elongation maximum strength".

[0044] The above tensile test can be carried out using a Tensilon tensile tester RTG-1210 manufactured by A&D Co., Ltd., in a thermostatic chamber for testing machines TLF-R3T-GA-PL manufactured by A&D Co., Ltd.

[0045] [Compared to unprocessed part] When the film F has the same layer structure as the film 10 and the scratched portion 30 is not formed, the test piece 40 is referred to as the test piece (reference test piece) 40a. Fig. 5 is also a schematic diagram of the test piece 40 being the test piece 40a.

[0046] A test piece 40 in which the film F has the same layer structure as the film 10 and the scratched portion 30 is formed is referred to as a test piece (first test piece or second test piece) 40b. FIG. 6 is a schematic diagram of the test piece 40b. The size example of the test piece 40b shown in FIG. 6 is the same as that in FIG. 5. The meaning of the hatched portion in FIG. 6 is also the same as that in FIG. 5. In the test piece 40b, the scratched portion 30 is located in the center of a pair of chucks when the test piece 40b is held by the pair of chucks, and is formed along the short side direction (corresponding to the MD direction). The ratio of the 5% stretched maximum strength of the test piece 40b to the 5% stretched maximum strength of the test piece 40a is defined as the "ratio of the unprocessed portion".

[0047] (Condition 1) In the case where the scratched portion 30 of the test piece 40b is the steam release portion 31, the ratio to the unprocessed portion is less than 75%.

[0048] (Condition 2) In the case where the scratched portion 30 of the test piece 40b is the steam release portion 31, the ratio to the unprocessed portion is 80% or more.

[0049] 7 to 12, examples of forming the scratched portion 30 (the steam release portion 31 or the opening induction portion 32) on the outer layer 12 will be described. The y-axis and z-axis directions shown in Figs. 7 to 12 are the same as the y-axis and z-axis directions shown in Figs. 2 and 3.

[0050] 7 to 10 are schematic diagrams showing examples of the formation of the scratched portion 30 when the layer structure of the film 10 is a three-layer structure. "The layer structure of the film 10 is an i-layer structure" means that the number of layers excluding a layer for joining two adjacent layers such as the adhesive layer 13 in the film 10 is i. i is an integer of 1 or more. FIG. 7 to FIG. 10 show examples of the formation of the scratched portion 30 in a form in which the film 10 has a sealant layer 11, a first resin layer 121, and a second resin layer 122. FIG. 7 to FIG. 10 are schematic diagrams of an example of a cross section perpendicular to the extension direction of the scratched portion 30 (the x-axis direction in FIG. 1).

[0051] 7 is a schematic diagram of a first forming example of the scratch processing part 30. The scratch processing part 30 of the first forming example is called scratch processing part 30P1. The scratch processing part 30P1 penetrates from the first resin layer 121 to the second resin layer 122. In other words, the scratch processing part 30P1 penetrates the outer layer 12, and the scratch processing part 30P1 is not formed in the sealant layer 11.

[0052] 8 is a schematic diagram of a second formation example of the scratch processing portion 30. The scratch processing portion 30 of the second formation example is referred to as the scratch processing portion 30P2. The scratch processing portion 30P2 is formed in the second resin layer 122. The scratch processing portion 30P2 penetrates the second resin layer 122. The scratch processing portion 30P2 is not formed in the first resin layer 121 and the sealant layer 11.

[0053] 9 is a schematic diagram of a third formation example of the scratch processing portion 30. The scratch processing portion 30 of the third formation example is referred to as the scratch processing portion 30P3. The scratch processing portion 30P3 is formed in the first resin layer 121. The scratch processing portion 30P3 penetrates the first resin layer 121. The scratch processing portion 30P3 is not formed in the second resin layer 122 and the sealant layer 11.

[0054] 10 is a schematic diagram of a fourth example of the scratch processing part 30. The scratch processing part 30 of the fourth example of the scratch processing part 30 is called the scratch processing part 30P4. The scratch processing part 30P4 is formed from the first resin layer 121 to the middle of the second resin layer 122. That is, the scratch processing part 30P4 does not penetrate the second resin layer 122 (or does not penetrate the outer layer 12). The scratch processing part 30P4 is formed, for example, from the surface of the second resin layer 122 on the first resin layer 121 side to about 1 / 3 or more and 4 / 5 or less of the thickness of the second resin layer 122. The scratch processing part 30P4 in the second resin layer 122 is not formed in the sealant layer 11.

[0055] Fig. 11 and Fig. 12 are schematic diagrams showing an example of the formation of the scratched portion 30 when the layer structure of the film 10 is a two-layer structure. Specifically, Fig. 11 and Fig. 12 show an example of the formation of the scratched portion 30 in an embodiment in which the film 10 has a sealant layer 11 and a first resin layer 121. Fig. 11 and Fig. 12 are also schematic diagrams of an example of a cross section perpendicular to the extension direction of the scratched portion 30 (the x-axis direction in Fig. 1).

[0056] 11 is a schematic diagram of a fifth formation example of the scratch processing portion 30. The scratch processing portion 30 of the fifth formation example is referred to as the scratch processing portion 30P5. The scratch processing portion 30P5 is formed in the first resin layer 121. The scratch processing portion 30P5 penetrates the first resin layer 121. In other words, the scratch processing portion 30P5 penetrates the outer layer 12. The scratch processing portion 30P5 is not formed in the sealant layer 11.

[0057] 12 is a schematic diagram of a sixth example of the scratch processing portion 30. The scratch processing portion 30 of the sixth example of the scratch processing portion 30 is referred to as the scratch processing portion 30P6. The scratch processing portion 30P6 is formed halfway through the first resin layer 121. In other words, the scratch processing portion 30P6 does not penetrate the outer layer 12. The scratch processing portion 30P6 is formed, for example, to about 1 / 3 or more and 4 / 5 or less of the thickness of the first resin layer 121. The scratch processing portion 30P6 is not formed in the sealant layer 11.

[0058] A film 10 having a steam release processed portion 31 and an opening induction processed portion 32 that satisfy the above conditions 1 and 2 may have a combination of the scratch processed portions 30P1 to 30P4 or a combination of the scratch processed portion P5 and the scratch processed portion 30P6, as shown in Table 1. [Table 1]

[0059] A description will be given of an example of a method for producing the film 10 having the combination examples S1 to S4 shown in Table 1. In the method for producing the film 10, the sealant layer 11, the second resin layer 122, and the first resin layer 121 are each a resin film.

[0060] <Example of a manufacturing method for the film 10 having the combination example 1> The scratched portion 30P2 is formed by sewing at a location of the second resin layer 122 where the opening induction processing portion 32 is to be formed. Specifically, the resin film corresponding to the second resin layer 122 is sewn while being fed in the MD direction. The sewing can be performed with a blade. In this embodiment, the scratched portion 30P2 is a perforation line along the MD direction.

[0061] Next, the sealant layer 11, the second resin layer 122 having the scratched portion 30P2, and the first resin layer 121 are laminated in this order to produce a laminated film. The laminated film can be produced by dry lamination. The sealant layer 11 and the second resin layer 122 are bonded together by an adhesive layer 13, and the second resin layer 122 and the first resin layer 121 are bonded together by an adhesive layer 13.

[0062] Thereafter, while the laminated film is being fed in the MD direction, scratch processed portion 30P1 is formed by laser processing at the location of laminated film where steam release processed portion 31 is to be formed. As a result, film 10 having scratch processed portion 30P1 and scratch processed portion 30P2 as steam release processed portion 31 and opening induction processed portion 32 is obtained.

[0063] The laser processing can be performed by irradiating the laminated film with a pulsed laser beam. The laser processing is performed, for example, using a CO2 laser device. In the laser processing, the desired scratch processing portion 30P1 can be formed by adjusting the laser power and the scanning speed.

[0064] <Example of a manufacturing method for the film 10 having the combination example 2> An example of a manufacturing method of the film 10 having the combination example 2 is similar to the combination example 1, except that instead of forming the scratch processing part 30P2 in the second resin layer 122, the scratch processing part 30P3 is formed by sewing in the first resin layer 121 at the location where the opening induction processing part 32 is to be formed. When forming the opening induction processing part 32 in the first resin layer 121, the resin film corresponding to the first resin layer 121 is subjected to sewing while flowing in the MD direction. The sewing can be performed by a blade. In this embodiment, the scratch processing part 30P3 is a perforation line along the MD direction.

[0065] <Example of a manufacturing method for the film 10 having the combination example 3> A laminated film is manufactured by laminating the sealant layer 11, the second resin layer 122, and the first resin layer 121 in this order. The laminated film can be manufactured by dry lamination. The sealant layer 11 and the second resin layer 122 are bonded to each other by the adhesive layer 13, and the second resin layer 122 and the first resin layer 121 are bonded to each other by the adhesive layer 13.

[0066] In the laminated film, the scratched portion 30P1 and the scratched portion 30P4 are formed by performing laser processing on the locations to be formed of the steam release processed portion 31 and the opening induction processed portion 32, respectively. In this way, the film 10 having the scratched portion 30P1 and the scratched portion 30P4 as the steam release processed portion 31 and the opening induction processed portion 32 is obtained.

[0067] The above laser processing is performed in the same manner as in the case of combination example 1. In the laser processing, the scratch processing portion 30P1 and the scratch processing portion 30P4 can be formed by adjusting the laser power and the scan speed.

[0068] <Example of a manufacturing method for the film 10 having the combination example 4> The sealant layer 11 and the first resin layer 121 are laminated in this order to produce a laminate film. The laminate film can be produced by dry lamination. The sealant layer 11 and the first resin layer 121 are bonded to each other by an adhesive layer 13.

[0069] In the laminated film, the scratched portion 30P5 and the scratched portion 30P6 are formed by performing laser processing on the planned formation locations of the steam release processed portion 31 and the opening induction processed portion 32. This results in a film 10 having the scratched portion 30P5 and the scratched portion 30P6 as the steam release processed portion 31 and the opening induction processed portion 32.

[0070] The above laser processing is performed in the same manner as in the case of combination example 1. In the laser processing, the scratch processing portion 30P5 and the scratch processing portion 30P6 can be formed by adjusting the laser power and the scan speed.

[0071] The packaging bag 1 using the film 10 has a steam release processed section 31. Therefore, the contents 100 can be heated while preventing the packaging bag 1 from bursting when heated in a microwave oven. The packaging bag 1 has an opening induction processed section 32, so that the contents 100 can be easily opened even if the contents 100 are sealed. Since the packaging bag 1 has the opening induction processed section 32, the contents 100 can be easily removed from the packaging bag 1. Since the contents 100 can be easily removed in this manner, even if the contents 100 contain liquid, the liquid is unlikely to spill when the contents 100 are removed.

[0072] The steam release processed portion 31 and the opening induction processed portion 32 are formed to satisfy conditions 1 and 2. Therefore, even if both the steam release processed portion 31 and the opening induction processed portion 32 are formed in the packaging bag 1, it is possible to selectively and appropriately release steam from the steam release processed portion 31, rather than from the opening induction processed portion 32, during microwave heating. Furthermore, because the opening induction processed portion 32 satisfies condition 2, the effect of thermal softening of the film 10 caused by microwave heating can be suppressed. Since the effect of thermal softening can be suppressed in this manner, the opening induction processed portion 32 can maintain appropriate cutting properties, and the packaging bag 1 can be easily opened using the opening induction processed portion 32.

[0073] By using a film having the same layer structure as film 10 constituting packaging bag 1, it is possible to obtain in advance the conditions for forming scratched portion 30 that satisfy both condition 1 and condition 2. By obtaining in advance the conditions for forming scratched portion in this manner, it is possible to manufacture packaging bag 1 that allows steam to be appropriately released during microwave heating and is easily openable after microwave heating. Therefore, with packaging bag 1, it is possible to improve the manufacturing yield.

[0074] Whether or not the film 10 having the steam release processed portion and the opening induction processed portion is suitable for the packaging bag 1 can be evaluated based on the conditions 1 and 2. In this respect, the packaging bag 1 can also achieve an improvement in the production yield.

[0075] In the packaging bag 1, by forming the opening induction processed portion 32, which is the scratch processed portion 30, the packaging bag 1 can be easily opened as described above. For example, it is not necessary to configure the film 10 using a functional film such as a film having linear cutting properties or a film having easy-to-cut properties. Therefore, the manufacturing cost of the packaging bag 1 can be reduced.

[0076] Next, an experimental example will be described regarding the film 10 and the packaging bag 1. For ease of explanation, in the explanation of the experimental example, the elements corresponding to the elements described in the explanation using Figs. 1 to 12 are given the same reference numerals, and duplicate explanations will be omitted.

[0077] (I) Experimental Examples 1 to 6 In Experimental Examples 1 to 6, a pillow-shaped packaging bag 1A shown in FIG. 13 was manufactured using the film F1. The packaging bag 1A had a tubular portion 2 made of a rectangular film F1, a first sealed portion 3 sealing a first end 2a of the tubular portion 2, and a second sealed portion 4 sealing a second end 2b of the tubular portion 2. In the packaging bag 1A, the direction along the central axis of the tubular portion 2 was the MD direction of the film F1. The tubular portion 2 had a back seal portion 5. The first seal portion 3, the second seal portion 4, and the back seal portion 5 were formed by heat-sealing the film F1. The x-axis direction and the y-axis direction shown in FIG. 13 are the same as the x-axis direction and the y-axis direction shown in FIG. 1.

[0078] The length of the packaging bag 1A in the x-axis direction was 170 mm. The length of the x-axis direction between the first sealed portion 3 and the second sealed portion 4 was 150 mm. The length of the packaging bag 1A in the y-axis direction was 150 mm. The back seal portion 5 was formed in the center in the y-axis direction. The widths of the first sealed portion 3, the second sealed portion 4, and the back seal portion 5 were 10 mm.

[0079] In Experimental Examples 1 to 6, a film without a scratched portion 30 and a film with a scratched portion 30 were prepared as the film F1. When the film F1 had the scratched portion 30, the packaging bag 1A had the scratched portion 30 along the x-axis direction at a position 75 mm from one of two opposing sides in the y-axis direction, as shown in Fig. 13. The length of the scratched portion 30 along the x-axis direction was 50 mm. [Experimental Example 1] In Experimental Example 1, a film F11a having no scratched portion 30 and films F11b and F11c having scratched portions 30 were prepared as the film F1 constituting the packaging bag 1A shown in FIG.

[0080] <Film F11a> The film F11a was a film having the layer structure X1 shown in Figure 14. In the layer structure X1, the first PET film (A), the second PET film (A) and the LLDPE film (C) correspond to the first resin layer 121, the second resin layer 122 and the sealant layer 11.

[0081] The first PET film (A) and the second PET film (A) used were GP012NV00W manufactured by Eikoh Kouki Co., Ltd. The first PET film (A) and the second PET film (A) had a thickness of 12 μm. The LLDPE film (C) used was LL-MTNST manufactured by Futamura Chemical Co., Ltd. The thickness of the LLDPE film (C) was 40 μm.

[0082] Film F11a was produced by laminating the LDPE film (C), the second PET film (A) and the first PET film (A) using an adhesive while they were being unwound from the original film. The conveying direction of the film unwound from the original film was the MD direction. For the adhesive, A626 manufactured by Mitsui Chemicals Inc. was used as the base agent, and A50 manufactured by Mitsui Chemicals Inc. was used as the hardener. The amount of adhesive applied was 3.4 g / m 2 It was.

[0083] <Film F11b> The film F11b was a film having the same layer structure X1 as the film F11a. The film F11b had a scratched portion 30P2 (see FIG. 8) formed as the scratched portion 30. Therefore, the film F1b was the same as the film F11a except that it had the scratched portion 30P2.

[0084] The film F11b was produced as follows. First, the second PET film (A) was perforated along the MD while being unwound from the original film, to form scratched portions 30P2 along the MD. The perforation was performed using a blade. Next, the LLDPE film (C), the second PET film (A) and the first PET film (A) were laminated in the same manner as in the production of the film F11a, except that the second PET film (A) having the scratched portions 30P2 was used. As a result, the film F11b was obtained.

[0085] <Film F11c> The film F11c was a film having the same layer structure X1 as the film F11a. The film F11c had a scratched portion 30P1 (FIG. 7) formed as the scratched portion 30. Therefore, the film F11c was the same as the film F11a except that it had the scratched portion 30P1.

[0086] The film F11c was produced by forming scratch processed portions 30P1 by laser processing a laminated film corresponding to the film F11a while flowing it in the MD direction.

[0087] The laser processing conditions were as follows: Laser device: Keyence 3Axis-CO2 laser marker / head ML-Z9510 Laser power: 25.2W Scan speed: 1200m / s

[0088] Experimental example 1 in which films F11a, F11b and F11c were used will be referred to as Experimental example 1a, Experimental example 1b and Experimental example 1c.

[0089] (1) Experimental Example 1a <Maximum internal pressure measurement and vapor permeability evaluation> A packaging bag 1A of Experimental Example 1a was prepared, which had a pressure measuring device and 100cc (100ml) of room temperature water inside. Specifically, a cylindrical portion 2 having a back seal portion 5 was formed using film F11a. Next, a first seal portion 3 was formed. After the pressure measuring device and 100cc of room temperature water were placed in the cylindrical portion 2 in which the first seal portion 3 was formed, a second seal portion 4 was formed. The pressure measuring device was placed in the packaging bag 1A so as to be buried in the room temperature water in the packaging bag 1A. The pressure measuring device used was "PicoVAQ PT" manufactured by TMI-Orion. Since film F11a did not have a scratched portion, the packaging bag 1A for Experimental Example 11a also did not have a scratched portion 30.

[0090] The packaging bag 1A prepared as described above was heated in a microwave oven at 500 W for 2 minutes. The microwave oven used was an MR-RY3000 manufactured by Hitachi, Ltd. The pressure change during microwave heating was measured in 0.25 second intervals, and the final highest pressure was taken as the "maximum internal pressure."

[0091] The maximum internal pressure was measured for each of the two packaging bags 1A for Experimental Example 11a, and the vapor permeability was evaluated. The vapor permeability was evaluated based on whether or not the heating was completed with the internal pressure at or above atmospheric pressure during the microwave heating.

[0092] The results of the maximum internal pressure measurement and the evaluation of vapor permeability are shown in Figure 15. In Figure 15, "N" in the "Maximum internal pressure" column is used to distinguish the measurement results for the two packaging bags 1A. The evaluations "A" and "B" in the "Vapor permeability" column were as follows: Evaluation "A": In both of the two packaging bags 1A, steam escaped during heating, and the heating was completed with the internal pressure maintained at or above atmospheric pressure (the bag did not break). Evaluation "B": At least one of the two packaging bags 1A was broken during heating and could no longer maintain pressure.

[0093] <5% stretching maximum strength> The film F11a was used as the film F of the test piece 40a shown in FIG. 5, and the "5% stretch maximum strength" was measured by the method described in the definition of [5% stretch maximum strength] above. The length of the test piece 40a in the long side direction was 150 mm. The distance between the pair of chucks was 100 mm. The tensile test to obtain the 5% stretch maximum strength was performed in a thermostatic chamber for testing machines TLF-R3T-GA-PL manufactured by A&D Co., Ltd., using a Tensilon tensile tester RTG-1210 manufactured by A&D Co., Ltd. The temperature in the thermostatic chamber during the tensile test was 100°C. The 5% stretch maximum strength of the film F11a was as shown in FIG. 15.

[0094] (2) Experimental Example 1b The maximum internal pressure measurement and the vapor permeability evaluation were carried out in the same manner as in Experimental Example 11a, except that Film F11b was used as Film F1.

[0095] Film F11b was used as film F in test piece 40b shown in FIG. 6, and "5% stretch maximum strength" was measured by the method described in the definition of [5% stretch maximum strength] above. The scratched portion 30 in test piece 40b was scratched portion 30P2. The length of test piece 40b in the long side direction was 150 mm. The distance between the pair of chucks was 100 mm. The measurement conditions for "5% stretch maximum strength" were the same as those in experimental example 1a.

[0096] The results of the maximum internal pressure measurement, the evaluation of vapor permeability, and the measurement of the maximum strength at 5% elongation are shown in FIG.

[0097] (3) Experimental Example 1c The maximum internal pressure measurement and the vapor permeability evaluation were carried out in the same manner as in Experimental Example 11a, except that Film F11c was used as Film F1.

[0098] Film F11c was used as film F in test piece 40b shown in FIG. 6, and "5% stretch maximum strength" was measured by the method described in the definition of [5% stretch maximum strength] above. The scratched portion 30 in test piece 40b was scratched portion 30P1. The length of test piece 40b in the long side direction was 150 mm. The distance between the pair of chucks was 100 mm. The measurement conditions for "5% stretch maximum strength" were the same as those in Experimental Example 1a.

[0099] The results of the maximum internal pressure measurement, the evaluation of vapor permeability, and the measurement of the maximum strength at 5% elongation are shown in FIG.

[0100] (4) Relative maximum strength at 5% elongation to unprocessed part The film F11a used in Experimental Example 1a does not have the scratched portion 30. Therefore, the measurement result of the maximum strength at 5% stretching obtained in Experimental Example 1a corresponds to the maximum strength at 5% stretching of the region (unprocessed portion) in the packaging bag 1A where the scratched portion 30 is not formed.

[0101] The ratio of the 5% stretch maximum strength measurement result obtained in Experimental Example 1b to the 5% stretch maximum strength measurement result obtained in Experimental Example 1a (ratio to the unprocessed part) and the ratio of the 5% stretch maximum strength measurement result obtained in Experimental Example 1c to the 5% stretch maximum strength measurement result obtained in Experimental Example 1a (ratio to the unprocessed part) were calculated. The calculation results are shown in FIG. 15.

[0102] [Experimental Example 2] In Experimental Example 2, a film F12a not having the scratched portion 30 and films F12b and F12c having the scratched portion 30 were prepared as the film F1 constituting the packaging bag 1A shown in FIG.

[0103] <Film F12a> Film F12a was a film having layer configuration X2 shown in Figure 14. Film F12a was the same as Film F11a, except that the second PET film (A) was replaced with a second PET film (B).

[0104] The second PET film (B) was PCBC manufactured by Toyobo Co., Ltd. The thickness of the second PET film (B) was 12 μm.

[0105] Film F12a was prepared in the same manner as film F11a, except that the second PET film (A) was replaced by a second PET film (B).

[0106] <Film F12b> The film F12b was a film having the same layer structure X2 as the film F12a. The film F12b had a scratched portion 30P3 (see FIG. 9) formed as the scratched portion 30. Therefore, the film F12b was the same as the film F12a except for having the scratched portion 30P3.

[0107] Film F12b was produced as follows. First, the first PET film (A) was perforated along the MD while being unwound from the original film, to form scratched portions 30P3 along the MD. The perforation was performed using a blade. Next, the LLDPE film (C), the second PET film (B) and the first PET film (A) were laminated in the same manner as in the case of film F11a, except that the first PET film (A) on which the scratched portions 30P3 were formed was used. As a result, film F12b was obtained.

[0108] <Film F12c> The film F12c was a film having the same layer structure X2 as the film F12a. The film F12c had a scratched portion 30P1 (see FIG. 7) formed as the scratched portion 30. Therefore, the film F12c was the same as the film F12a except for having the scratched portion 30P1.

[0109] The film F12c was produced by forming the scratched portion 30P1 by laser processing while flowing the laminated film corresponding to the film F12a in the MD direction. The laser processing conditions were the same as those for the film F11c.

[0110] Experimental Example 2 in which the above-mentioned films F12a, F12b and F12c were used will be referred to as Experimental Example 2a, Experimental Example 2b and Experimental Example 2c.

[0111] (1) Experimental Example 2a In Experimental Example 2a, the maximum internal pressure measurement and the vapor permeability evaluation were performed in the same manner as in Experimental Example 1a, except that the film F12a was used instead of the film F11a. The "5% stretch maximum strength" was measured in the same manner as in Example 1a, except that the film F12a was used as the film F of the test piece 40a shown in FIG. 5. The results of the maximum internal pressure measurement, the vapor permeability evaluation, and the measurement results of the 5% stretch maximum strength are shown in FIG. (2) Experimental Example 2b In Experimental Example 2b, the maximum internal pressure measurement and the vapor permeability evaluation were performed in the same manner as in Experimental Example 1a, except that the film F12b was used instead of the film F11a. The "5% stretch maximum strength" was measured in the same manner as in Example 1b, except that the film F12b was used as the film F of the test piece 40b shown in FIG. 6. The scratched portion 30 of the test piece 40b was the scratched portion 30P3. The results of the maximum internal pressure measurement, the vapor permeability evaluation, and the measurement results of the 5% stretch maximum strength were as shown in FIG. 15.

[0112] (3) Experimental Example 2c In Experimental Example 2c, the maximum internal pressure measurement and the vapor permeability evaluation were performed in the same manner as in Experimental Example 1a, except that the film F12c was used instead of the film F11a. The "5% stretch maximum strength" was measured in the same manner as in Example 1c, except that the film F12c was used as the film F of the test piece 40b shown in FIG. 6. The scratched portion 30 of the test piece 40b was the scratched portion 30P1. The results of the maximum internal pressure measurement, the vapor permeability evaluation, and the measurement results of the 5% stretch maximum strength were as shown in FIG. 15.

[0113] (4) Relative maximum strength at 5% elongation to unprocessed part The film F12a used in Experimental Example 2a does not have the scratched portion 30. Therefore, the measurement result of the maximum strength at 5% stretch obtained in Experimental Example 2a corresponds to the maximum strength at 5% stretch of the region (unprocessed portion) where the scratched portion is not formed in the packaging bag 1A of Experimental Examples 2b and 2c.

[0114] The ratio of the 5% stretch maximum strength measurement result obtained in Experimental Example 2b to the 5% stretch maximum strength measurement result obtained in Experimental Example 2a (ratio to the unprocessed part) and the ratio of the 5% stretch maximum strength measurement result obtained in Experimental Example 2c to the 5% stretch maximum strength measurement result obtained in Experimental Example 2a (ratio to the unprocessed part) were calculated. The calculation results are shown in FIG. 15.

[0115] [Experimental Example 3] In Experimental Example 3, a film F13a not having the scratched portion 30 and films F13b and F13c having the scratched portion 30 were prepared as the film F1 constituting the packaging bag 1A shown in FIG.

[0116] <Film F13a> Film F13a was a film having layer configuration X3 shown in Figure 14. Film F13a was the same as Film F11a, except that the second PET film (A) was replaced with a second PET film (B).

[0117] The second PET film (B) was PCBC manufactured by Toyobo Co., Ltd. The thickness of the second PET film (B) was 12 μm.

[0118] Film F13a was prepared in the same manner as film F11a, except that the second PET film (A) was replaced by a second PET film (B).

[0119] <Film F13b> The film F13b was a film having the same layer structure X3 as the film F13a. The film F13b had a scratched portion 30P4 (see FIG. 10) formed as the scratched portion 30. Therefore, the film F13b was the same as the film F13a except for having the scratched portion 30P4.

[0120] The film F13b was produced by forming scratched portions 30P4 by laser processing while flowing a laminated film corresponding to the film F13a in the MD direction.

[0121] The laser processing conditions were the same as those for film F11c, except that the laser power was changed to 12.6 W and the scanning speed was changed to 2000 m / s.

[0122] <Film F13c> The film F13c was a film having the same layer structure X3 as the film F13a. The film F13c had a scratched portion 30P1 (see FIG. 7) formed as the scratched portion 30. Therefore, the film F13c was the same as the film F13a except for having the scratched portion 30P1.

[0123] The film F13c was produced by forming the scratched portion 30P1 by laser processing while flowing the laminated film corresponding to the film F13a in the MD direction. The laser processing conditions were the same as those for the film F11c.

[0124] Experimental Example 3 in which the above-mentioned films F13a, F13b and F13c were used will be referred to as Experimental Example 3a, Experimental Example 3b and Experimental Example 3c.

[0125] (1) Experimental Example 3a In Experimental Example 3a, the maximum internal pressure measurement and the vapor permeability evaluation were performed in the same manner as in Experimental Example 1a, except that the film F13a was used instead of the film F11a. The "5% stretch maximum strength" was measured in the same manner as in Example 1a, except that the film F13a was used as the film F of the test piece 40a shown in FIG. 5. The results of the maximum internal pressure measurement, the vapor permeability evaluation, and the measurement results of the 5% stretch maximum strength are shown in FIG.

[0126] (2) Experimental Example 3b In Experimental Example 3b, the maximum internal pressure measurement and the vapor permeability evaluation were performed in the same manner as in Experimental Example 1a, except that the film F13b was used instead of the film F11b. The "5% stretch maximum strength" was measured in the same manner as in Example 1b, except that the film F13b was used as the film F of the test piece 40b shown in FIG. 6. The scratched portion 30 of the test piece 40b was the scratched portion 30P4. The results of the maximum internal pressure measurement, the vapor permeability evaluation, and the measurement results of the 5% stretch maximum strength were as shown in FIG. 15.

[0127] (3) Experimental Example 3c In Experimental Example 3c, the maximum internal pressure measurement and the vapor permeability evaluation were performed in the same manner as in Experimental Example 13c, except that the film F13c was used instead of the film F11c. The "5% stretch maximum strength" was measured in the same manner as in Example 1c, except that the film F13c was used as the film F of the test piece 40b shown in FIG. 6. The scratched portion 30 of the test piece 40b was the scratched portion 30P1. The results of the maximum internal pressure measurement, the vapor permeability evaluation, and the measurement results of the 5% stretch maximum strength were as shown in FIG. 15.

[0128] (4) Relative maximum strength at 5% elongation to unprocessed part The film F13a used in Experimental Example 3a did not have a scratched portion, and therefore the measurement result of the maximum strength at 5% stretch obtained in Experimental Example 3a corresponds to the maximum strength at 5% stretch of the region (unprocessed portion) where no scratched portion is formed in the packaging bag 1A in Experimental Examples 3b and 3c.

[0129] The ratio of the 5% stretch maximum strength measurement result obtained in Experimental Example 3b to the 5% stretch maximum strength measurement result obtained in Experimental Example 3a (ratio to the unprocessed part) and the ratio of the 5% stretch maximum strength measurement result obtained in Experimental Example 3c to the 5% stretch maximum strength measurement result obtained in Experimental Example 3a (ratio to the unprocessed part) were calculated. The calculation results are shown in FIG. 15.

[0130] [Experimental Example 4] In Experimental Example 4, a film F14a not having the scratched portion 30 and films F14b and F14c having the scratched portion 30 were prepared as the film 1F constituting the packaging bag 1A shown in FIG.

[0131] <Film F14a> The film F14a was a film having the layer structure X4 shown in Fig. 14. In the layer structure X4, the first PET film (A) and the LLDPE film (C) correspond to the first resin layer 121 and the sealant layer 11.

[0132] The first PET film (A) used was GP012NV00W manufactured by Eikoh Kouki Co., Ltd. The thickness of the first PET film (A) was 12 μm. The LLDPE film (C) used was LL-MTNST manufactured by Futamura Chemical Co., Ltd. The thickness of the LLDPE film (C) was 40 μm.

[0133] Film F14a was produced in the same manner as film F11a, except that the second PET film (A) was not used.

[0134] <Film F14b> The film F14b was a film having the same layer structure X4 as the film F14a. The film F14b had a scratched portion 30P6 (see FIG. 12) formed as the scratched portion 30. Therefore, the film F14b was the same as the film F14a except for having the scratched portion 30P6.

[0135] The film F14b was produced by forming scratch processed portions 30P6 by laser processing a laminated film corresponding to the film F14a while flowing it in the MD direction.

[0136] The laser processing conditions were the same as those for film F11c, except that the laser power was changed to 9.45 W and the scanning speed was changed to 2000 m / s.

[0137] <Film F14c> The film F14c was a film having the same layer structure X4 as the film F14a. The film F14c had a scratched portion 30P5 (see FIG. 11) formed as the scratched portion 30. Therefore, the film F14c was the same as the film F14a except for having the scratched portion 30P5.

[0138] The film F14c was produced by forming the scratched portion 30P5 by laser processing while flowing the laminated film corresponding to the film F14a in the MD direction. The laser processing conditions were the same as those for the film F11c.

[0139] Experimental Example 4 in which the above-mentioned films F14a, F14b and F14c were used will be referred to as Experimental Example 4a, 4b and 4c.

[0140] (1) Experimental Example 4a In Experimental Example 4a, the maximum internal pressure measurement and the vapor permeability evaluation were performed in the same manner as in Experimental Example 1a, except that the film F14a was used instead of the film F11a. The "5% stretch maximum strength" was measured in the same manner as in Example 1a, except that the film F14a was used as the film F of the test piece 40a shown in FIG. 5. The results of the maximum internal pressure measurement, the vapor permeability evaluation, and the measurement results of the 5% stretch maximum strength are shown in FIG.

[0141] (2) Experimental Example 4b In Experimental Example 4b, the maximum internal pressure measurement and the vapor permeability evaluation were performed in the same manner as in Experimental Example 11b, except that the film F14b was used instead of the film F11b. The "5% stretch maximum strength" was measured in the same manner as in Example 1b, except that the film F14b was used as the film F of the test piece 40b shown in FIG. 6. The scratched portion 30 of the test piece 40b was the scratched portion 30P6. The results of the maximum internal pressure measurement, the vapor permeability evaluation, and the measurement results of the 5% stretch maximum strength were as shown in FIG. 15.

[0142] (3) Experimental Example 4c In Experimental Example 4c, the maximum internal pressure measurement and the vapor permeability evaluation were performed in the same manner as in Experimental Example 13c, except that the film F14c was used instead of the film F11c. The "5% stretch maximum strength" was measured in the same manner as in Example 1c, except that the film F14c was used as the film F of the test piece 40b shown in FIG. 6. The scratched portion 30 of the test piece 40b was the scratched portion 30P5. The results of the maximum internal pressure measurement, the vapor permeability evaluation, and the measurement results of the 5% stretch maximum strength were as shown in FIG. 15.

[0143] (4) Relative maximum strength at 5% elongation to unprocessed part The film F14a used in the experimental example 4a did not have a scratched portion. Therefore, the measurement result of the maximum strength at 5% stretch obtained in the experimental example 4a corresponds to the maximum strength at 5% stretch of the region (unprocessed portion) where no scratched portion is formed in the packaging bag 1A of the experimental examples 4b and 4c.

[0144] The ratio of the 5% stretch maximum strength measurement result obtained in Experimental Example 4b to the 5% stretch maximum strength measurement result obtained in Experimental Example 4a, and the ratio of the 5% stretch maximum strength measurement result obtained in Experimental Example 4c to the 5% stretch maximum strength measurement result obtained in Experimental Example 4a were calculated. The calculation results were as shown in the figure.

[0145] [Experimental Example 5] In Experimental Example 5, as the film F1 constituting the packaging bag 1A shown in FIG. 13, a film F15a not having the scratched portion 30 and films F15b and F15c having the scratched portion 30 were prepared.

[0146] <Film F15a> Film F15a was a film having layer structure X5 shown in FIG. 14. Film F15a was the same as film F14a, except that LLDPE film (D) was used instead of LLDPE film (C). KF101 manufactured by Sky Film Co., Ltd. was used as LLDPE film (D). Film F15a was produced in the same manner as film F14a, except that LLDPE film (D) was used instead of LLDPE film (D) (C).

[0147] <Film F15b> The film F15b was a film having the same layer structure X4 as the film F15a. The film F15b had a scratched portion 30P6 (see FIG. 12) formed as the scratched portion 30. Therefore, the film F15b was the same as the film F15a except for having the scratched portion 30P6.

[0148] Film F15b was produced by forming scratch processing portion 30P6 by laser processing while flowing a laminated film corresponding to film F14a in the MD direction. The laser processing conditions were the same as those for film F11c, except that the laser power was changed to 12.6 W and the scan speed was changed to 2000 m / s.

[0149] <Film F15c> The film F15c was a film having the same layer structure X4 as the film F15a. The film F15c had a scratched portion 30P5 (see FIG. 11) formed as the scratched portion 30. Therefore, the film F15c was the same as the film F15a except for having the scratched portion 30P5.

[0150] The film F15c was produced by forming the scratched portion 30P5 by laser processing while flowing the laminated film corresponding to the film F15a in the MD direction. The laser processing conditions were the same as those for the film F11c.

[0151] Experimental Example 5 in which the above-mentioned films F15a, F15b and F15c were used will be referred to as Experimental Example 5a, Experimental Example 5b and Experimental Example 5c.

[0152] (1) Experimental Example 5a In Experimental Example 5a, the maximum internal pressure measurement and the vapor permeability evaluation were performed in the same manner as in Experimental Example 1a, except that the film F15a was used instead of the film F11a. The "5% stretch maximum strength" was measured in the same manner as in Example 1a, except that the film F15a was used as the film F of the test piece 40a shown in FIG. 5. The results of the maximum internal pressure measurement, the vapor permeability evaluation, and the measurement results of the 5% stretch maximum strength are shown in FIG.

[0153] (2) Experimental Example 5b In Experimental Example 5b, the maximum internal pressure measurement and the vapor permeability evaluation were performed in the same manner as in Experimental Example 11b, except that the film F15b was used instead of the film F11b. The "5% stretch maximum strength" was measured in the same manner as in Example 1b, except that the film F15b was used as the film F of the test piece 40b shown in FIG. 6. The scratched portion 30 of the test piece 40b was the scratched portion 30P6. The results of the maximum internal pressure measurement, the vapor permeability evaluation, and the measurement results of the 5% stretch maximum strength were as shown in FIG. 15.

[0154] (3) Experimental Example 5c In Experimental Example 5c, the maximum internal pressure measurement and the vapor permeability evaluation were performed in the same manner as in Experimental Example 11c, except that the film F15c was used instead of the film F11c. The "5% stretch maximum strength" was measured in the same manner as in Example 1c, except that the film F15c was used as the film F of the test piece 40b shown in FIG. 6. The scratched portion 30 of the test piece 40b was the scratched portion 30P5. The results of the maximum internal pressure measurement, the vapor permeability evaluation, and the measurement results of the 5% stretch maximum strength were as shown in FIG. 15.

[0155] (4) Relative maximum strength at 5% elongation to unprocessed part The film F15a used in the experimental example 5a does not have a scratched portion. Therefore, the measurement result of the maximum strength at 5% stretch obtained in the experimental example 5a corresponds to the maximum strength at 5% stretch of the region (unprocessed portion) where no scratched portion is formed in the packaging bag 1A in the experimental examples 5b and 5c.

[0156] The ratio of the 5% stretch maximum strength measurement result obtained in Experimental Example 5b to the 5% stretch maximum strength measurement result obtained in Experimental Example 5a, and the ratio of the 5% stretch maximum strength measurement result obtained in Experimental Example 5c to the 5% stretch maximum strength measurement result obtained in Experimental Example 5a were calculated. The calculation results are shown in FIG.

[0157] [Experimental Example 6] In Experimental Example 6, a film F16a not having the scratched portion 30 and films F16b and F16c having the scratched portion 30 were prepared as the film F1 constituting the packaging bag 1A shown in FIG.

[0158] <Film F16a> The film F16a had the layer structure X6 shown in FIG. 14. The layer structure X6 was the same as the film F15a, except that an ONY film was used instead of the first PET film (A) in the layer structure X5. The thickness of the ONY film was 15 μm. The ONY film was ON manufactured by Unitika Ltd. The film F16a was produced in the same manner as the film F15a, except that an ONY film was used instead of the first PET film (A).

[0159] <Film F16b> The film F16b was a film having the same layer structure X6 as the film F16a. The film F16b had a scratched portion 30P6 (see FIG. 12) formed as the scratched portion 30. Therefore, the film F16b was the same as the film F16a except for having the scratched portion 30P6.

[0160] The film F16b was produced by forming the scratched portion 30P6 by laser processing while flowing the laminated film corresponding to the film F16a in the MD direction. The laser processing conditions were the same as those for the film F15b.

[0161] <Film F16c> The film F16c had the same layer structure as the film F16a. The film F16c had a scratched portion 30P5 (see FIG. 11) formed as the scratched portion 30. Therefore, the film F16c was the same as the film F16a except for having the scratched portion 30P5.

[0162] Film F16c was produced by forming scratch processing portion 30P5 by laser processing while flowing a laminated film corresponding to film F16a in the MD direction. The laser processing conditions were the same as those for film F11c, except that the scanning speed was changed to 800 m / s.

[0163] Experimental Example 6 in which the above-mentioned films F16a, F16b and F16c were used will be referred to as Experimental Example 6a, Experimental Example 6b and Experimental Example 6c.

[0164] (1) Experimental Example 6a In Experimental Example 6a, the maximum internal pressure measurement and the vapor permeability evaluation were performed in the same manner as in Experimental Example 1a, except that the film F16a was used instead of the film F11a. The "5% stretch maximum strength" was measured in the same manner as in Example 1a, except that the film F16a was used as the film F of the test piece 40a shown in FIG. 5. The results of the maximum internal pressure measurement, the vapor permeability evaluation, and the measurement results of the 5% stretch maximum strength are shown in FIG. 15.

[0165] (2) Experimental Example 6b In Experimental Example 6b, the maximum internal pressure measurement and the vapor permeability evaluation were performed in the same manner as in Experimental Example 11b, except that the film F16b was used instead of the film F11b. The scratched portion 30 of the test piece 40b for which the "5% stretch maximum strength" was measured was the scratched portion 30P6, in the same manner as in Example 1b, except that the film F16b was used as the film F of the test piece 40b shown in FIG. 6. The results of the maximum internal pressure measurement, the vapor permeability evaluation, and the measurement results of the 5% stretch maximum strength are shown in FIG. 15.

[0166] (3) Experimental Example 6c In Experimental Example 6c, the maximum internal pressure measurement and the vapor permeability evaluation were performed in the same manner as in Experimental Example 11c, except that the film F16c was used instead of the film F11c. The "5% stretch maximum strength" was measured in the same manner as in Example 1c, except that the film F16c was used as the film F of the test piece 40b shown in FIG. 6. The scratched portion 30 of the test piece 40b was the scratched portion 30P5. The results of the maximum internal pressure measurement, the vapor permeability evaluation, and the measurement results of the 5% stretch maximum strength were as shown in FIG. 15.

[0167] (4) Relative maximum strength at 5% elongation to unprocessed part The film F16a used in Experimental Example 6a did not have a scratched portion. Therefore, the measurement result of the maximum strength at 5% stretch obtained in Experimental Example 6a corresponds to the maximum strength at 5% stretch of the region (unprocessed portion) where no scratched portion is formed in the packaging bag 1A of Experimental Examples 6b and 6c.

[0168] In Experimental Example 6, the ratio of the 5% stretch maximum strength measurement result obtained in Experimental Example 6b to the 5% stretch maximum strength measurement result obtained in Experimental Example 5a (ratio to the unprocessed part) and the ratio of the 5% stretch maximum strength measurement result obtained in Experimental Example 6c to the 5% stretch maximum strength measurement result obtained in Experimental Example 6a (ratio to the unprocessed part) were calculated. The calculation results are shown in FIG. 15.

[0169] <Processing type and processing strength> The processing type of the scratch processing part determined by the combination of the layer configuration and the scratch processing part may be called as shown in FIG. 16. For example, as shown in FIG. 16, the combination of the layer configuration X1 and the scratch processing part 30P2 is called processing type T1a, and the combination of the layer configuration X1 and the scratch processing part 30P1 is called processing type T1b. Similarly, the combination of the layer configuration X2 and the scratch processing part 30P3 is called processing type T2a, and the combination of the layer configuration X2 and the scratch processing part 30P1 is called processing type T2b. The processing types based on the combinations of the other layer configurations X3 to X6 and the scratch processing parts 30P1, 30P4, 30P5, and 30P6 are as shown in FIG.

[0170] FIG. 16 is a chart in which the smallest measurement result of the “ratio to the unprocessed area” for each of the experimental examples 1 to 6 shown in FIG. 15 is designated as “strong” processing, and any measurement result greater than that is designated as “weak” processing, and the chart is organized according to the processing type shown in FIG. 16.

[0171] <Maximum internal pressure evaluation> The maximum internal pressure measurements shown in Fig. 15 are organized according to the processing strength shown in Fig. 16. Fig. 17 is a chart in which the maximum internal pressure measurements shown in Fig. 15 correspond to the "strong" processing and "weak" processing shown in Fig. 16. In Fig. 17, the maximum internal pressure measurements are arranged in the "weak" and "strong" processing strength columns so that the numerical values ​​decrease from left to right.

[0172] Considering the results of vapor permeability in Fig. 15 and the results in Fig. 17, when the processing strength is "weak", appropriate vapor permeability is not obtained, whereas when the processing strength is "strong", appropriate vapor permeability is obtained. Therefore, from the results shown in Fig. 17, it can be understood that appropriate vapor permeability can be ensured if the maximum internal pressure when the packaging bag 1A (inner dimensions: 150 mm x 150 mm) having the scratched portion 30 is heated at 500 W for 2 minutes is 0.113 MPa or less.

[0173] (II) Experimental Examples 7-12 In Experimental Examples 7 to 12, the packaging bag 1B shown in FIG. 18 was manufactured using the film F2. The packaging bag 1B had a tubular portion 2 made of a rectangular film F2, a first sealed portion 3 sealing the first end 2a of the tubular portion 2, and a second sealed portion 4 sealing the second end 2b of the tubular portion 2. In the packaging bag 1B, the direction along the central axis of the tubular portion 2 was the MD direction of the film F2. The tubular portion 2 had a back seal portion 5. The first seal portion 3, the second seal portion 4, and the back seal portion 5 were formed by heat sealing the film F1. The x-axis direction and the y-axis direction shown in FIG. 18 are the same as the x-axis direction and the y-axis direction shown in FIG. 1.

[0174] The length of the packaging bag 1B in the x-axis direction was 120 mm. The length of the x-axis direction between the first sealed portion 3 and the second sealed portion 4 was 100 mm. The length of the packaging bag 1B in the y-axis direction was also 100 mm. The back seal portion 5 was formed in the center in the y-axis direction. The widths of the first sealed portion 3, the second sealed portion 4, and the back seal portion 5 were 10 mm.

[0175] The packaging bag 1B had a steam release processed part and an opening induction processed part at positions where the same pressure acts during microwave heating. In the explanation of Experimental Examples 7 to 12, for convenience of explanation, the steam release processed part that does not satisfy condition 1 will also be referred to as the steam release processed part 31, and the opening induction processed part that does not satisfy condition 2 will also be referred to as the opening induction processed part 32. Specifically, the steam release processed part 31 and the opening induction processed part 32 were formed at a position 30 mm from the central position in the y-axis direction of the packaging bag 1B (positions 50 mm from both sides in the y-axis direction). As shown in FIG. 18, the steam release processed part 31 and the opening induction processed part 32 were formed opposite to each other with respect to the central position in the y-axis direction of the packaging bag 1B. The length of the steam release processed part 31 along the x-axis direction was 50 mm.

[0176] [Experimental Example 7] In Experimental Example 7, films F21a, F21b, and F21c were prepared as the film F2 constituting the packaging bag 1B shown in FIG.

[0177] <Film F21a> The film F21a had a layer structure X1 (see FIG. 14), and was a film in which the scratched portion 30P2 was adopted as the steam release processed portion 31 and the opening induction processed portion 32. The steam release processed portion 31 and the opening induction processed portion 32 in the film F21a were scratched portions of the processing type 1a, and the processing strength was "weak."

[0178] The film F21a was produced as follows. In the same manner as in the case of the film F11b, the scratched portion 30P2 was formed in the second PET film (A) at the location where the steam release portion 31 and the opening induction portion 32 were to be formed. After that, the LLDPE film (C), the second PET film (A) and the first PET film (A) were laminated in the same manner as in the case of producing the film F11a, except that the second PET film (A) on which the scratched portion 30P2 was formed was used. As a result, the film F21a was obtained.

[0179] <Film F21b> Film F21b had layer structure X1, and was a film in which scratched portion 30P1 was used as steam release processed portion 31 and scratched portion 30P2 was used as opening induction processed portion 32. The steam release processed portion 31 in film F21b was a scratched portion of processing type T1b, and the processing strength was "strong." The opening induction processed portion 32 in film F21b was a scratched portion of processing type T1a, and the processing strength was "weak."

[0180] The film F21b was produced as follows. In the same manner as in the case of the film F11b, a scratch processing portion 30P2 was formed in the second PET film (A) at a location where the opening induction processing portion 32 was to be formed. Thereafter, the LLDPE film (C), the second PET film (A) and the first PET film (A) were laminated in the same manner as in the case of producing the film F11a, except that the second PET film (A) on which the scratch processing portion 30P2 was formed was used, to obtain a laminated film having the LLDPE film (C), the second PET film (A) and the first PET film (A). In the laminated film, a scratch processing portion 30P1 was formed in the location where the steam release processing portion 31 was to be formed in the same manner as in the case of the film F11c. As a result, the film F21b was obtained.

[0181] <Film F22c> The film F22c had a layer structure X1, and was a film in which the scratched portion 30P1 was adopted as the steam release processed portion 31 and the opening induction processed portion 32. The steam release processed portion 31 and the opening induction processed portion 32 in the film F22c were scratched portions of the processing type T1b, and the processing strength was "strong".

[0182] Film F22c was produced by producing a laminated film corresponding to film F12a in the same manner as film F12a, and then, while flowing the laminated film in the MD direction, forming scratch processing portion 30P1 at the intended locations for forming steam release processing portion 31 and opening induction processing portion 32 in the same manner as film F12c.

[0183] (1) Experimental Example 7a By using the film F21a as the film F2, a packaging bag 1B was prepared that was sealed while containing 100 cc of room temperature water.

[0184] The prepared packaging bag 1B was heated for 1 minute and 30 seconds at 500 W in a microwave oven. The microwave oven used was an MR-RY3000 manufactured by Hitachi, Ltd.

[0185] (Evaluation of steam release processing part) The steam release processed portion 31 was evaluated for its steam permeability during microwave heating. An evaluation was made as to whether or not steam selectively escapes from the steam release processed portion 31 without the packaging bag 1B rupturing during microwave heating. Specifically, in Experimental Example 7a, a case in which the packaging bag 1B did not rupture and steam selectively escaped from the steam release processed portion 31 during microwave heating was evaluated as "steam permeable", and other cases were evaluated as "non-steam permeable". Cases in which the packaging bag 1B ruptures are also included.

[0186] (Evaluation of opening induction processing part) The opening induction processed part 32 was evaluated based on the change in width of the opening induction processed part 32 after microwave heating relative to the width of the opening induction processed part 32 before microwave heating (before heating up from the microwave) (hereinafter referred to as the "width change rate"). Specifically, when the width change rate was within 150%, it was evaluated as "no change", and when the width change rate exceeded 150%, it was evaluated as "stretched".

[0187] (2) Experimental Example 7b The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in Experimental Example 7a, except that the film F21b was used as the film F2.

[0188] (3) Experimental Example 7c The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in Experimental Example 7a, except that the film F21c was used as the film F2.

[0189] [Experimental Example 8] In Experimental Example 8, films F22a, F22b, and F22c were prepared as the film F2 constituting the packaging bag 1B shown in FIG.

[0190] <Film F22a> The film F22a had a layer structure X2, and was a film in which the scratched portion 30P3 was adopted as the steam release processed portion 31 and the opening induction processed portion 32. The steam release processed portion 31 and the opening induction processed portion 32 in the film F22a were scratched portions of the processing type T2a, and the processing strength was "weak".

[0191] The film F22a was produced as follows. In the same manner as in the case of the film F12b, the scratched portion 30P3 was formed in the first PET film (A) at the location where the steam release portion 31 and the opening induction portion 32 were to be formed. After that, the LLDPE film (C), the second PET film (B) and the first PET film (A) were laminated in the same manner as in the case of producing the film F12a, except that the first PET film (A) on which the scratched portion 30P3 was formed was used. As a result, the film F22a was obtained.

[0192] <Film F22b> Film F22b had layer structure X2, and was a film in which scratched portion 30P1 was used as steam release processed portion 31, and scratched portion 30P3 was used as opening induction processed portion 32. The steam release processed portion 31 in film F22b was a scratched portion of processing type T2b, and the processing strength was "strong." The opening induction processed portion 32 in film F22b was a scratched portion of processing type T2a, and the processing strength was "weak."

[0193] The film F22b was produced as follows. In the same manner as in the case of the film F12b, a scratch processing portion 30P3 was formed in the first PET film (A) at a location where the opening induction processing portion 32 was to be formed. Thereafter, the LLDPE film (C), the second PET film (B) and the first PET film (A) were laminated in the same manner as in the case of producing the film F12a, except that the first PET film (A) on which the scratch processing portion 30P3 was formed was used, to obtain a laminated film having the LLDPE film (C), the second PET film (B) and the first PET film (A). In the laminated film, a scratch processing portion 30P1 was formed in the location where the steam release processing portion 31 was to be formed in the same manner as in the case of the film F12c. As a result, the film F22b was obtained.

[0194] <Film F22c> The film F22c had a layer structure X2, and was a film in which the scratched portion 30P1 was adopted as the steam release processed portion 31 and the opening induction processed portion 32. The steam release processed portion 31 and the opening induction processed portion 32 in the film F21c were scratched portions of the processing type T2b, and the processing strength was "strong".

[0195] Film F22c was produced by producing a laminated film corresponding to film F12a in the same manner as film F12a, and then, while flowing the laminated film in the MD direction, forming scratch processed portions 30P1 at the formation positions of the steam release processed portion 31 and the opening induction processed portion 32 in the same manner as film F12c.

[0196] (1) Experimental Example 8a The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in experimental example 7a, except that film F21a was used as film F2 constituting the packaging bag 1B shown in Figure 18.

[0197] (2) Experimental Example 8b The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in experimental example 7a, except that film F21b was used as film F2 constituting the packaging bag 1B shown in Figure 18.

[0198] (3) Experimental Example 8c The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in experimental example 7a, except that film F21c was used as film F2 constituting the packaging bag 1B shown in Figure 18.

[0199] [Experimental Example 9] In Experimental Example 9, films F23a, F23b, and F23c were prepared as the film F2 constituting the packaging bag 1B shown in FIG.

[0200] <Film F23a> The film F23a had a layer structure X3, and was a film in which the scratched portion 30P4 was adopted as the steam release processed portion 31 and the opening induction processed portion 32. The steam release processed portion 31 and the opening induction processed portion 32 in the film F23a were scratched portions of the processing type T3, and the processing strength was "weak".

[0201] The film F23a was produced as follows: A laminated film corresponding to the film F13a was produced in the same manner as the film F13a, and then the laminated film was fed in the MD direction, and the scratched portions 30P4 were formed in the locations where the steam release portion 31 and the opening induction portion 32 were to be formed in the same manner as the film F13b.

[0202] <Film F23b> Film F23 had layer structure X3, and scratched portion 30P1 was used as steam release processed portion 31, and scratched portion 30P4 was used as opening induction processed portion 32. The steam release processed portion 31 in film F23b was a scratched portion of processing type T3b, and the processing strength was "strong." The opening induction processed portion 32 in film F23b was a scratched portion of processing type T3a, and the processing strength was "weak."

[0203] The film F23b was produced as follows. After producing a laminated film corresponding to the film F13a in the same manner as the film F13a, the laminated film was fed in the MD direction, and the scratched portion 30P4 was formed at the intended location for the opening induction portion 32 in the same manner as the film F13b, and the scratched portion 30P1 was formed at the intended location for the steam release portion 31 in the same manner as the film F13c. As a result, the film F23b was obtained.

[0204] <Film F23c> The film F23c had a layer structure X2, and was a film in which the scratched portion 30P1 was adopted as the steam release processed portion 31 and the opening induction processed portion 32. The steam release processed portion 31 and the opening induction processed portion 32 in the film F23c were scratched portions of the processing type T3b, and the processing strength was "strong".

[0205] Film F23c was produced in the same manner as film F13a by producing a laminated film corresponding to film F13a, and then, while flowing the laminated film in the MD direction, forming scratch processing portion 30P1 at the intended locations for forming steam release processing portion 31 and opening induction processing portion 32, in the same manner as film F13c.

[0206] (1) Experimental Example 9a The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in experimental example 7a, except that film F22a was used as film F2 constituting the packaging bag 1B shown in Figure 18.

[0207] (2) Experimental Example 9b The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in experimental example 7a, except that film F22b was used as film F2 constituting the packaging bag 1B shown in Figure 18.

[0208] (3) Experimental Example 9c The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in experimental example 7a, except that film F22c was used as film F2 constituting the packaging bag 1B shown in Figure 18.

[0209] [Experimental Example 10] In Experimental Example 10, films F24a, F24b, and F24c were prepared as the film F2 constituting the packaging bag 1B shown in FIG.

[0210] <Film F24a> The film F24a had a layer structure X4, and was a film in which the scratched portion 30P6 was adopted as the steam release processed portion 31 and the opening induction processed portion 32. The steam release processed portion 31 and the opening induction processed portion 32 in the film F24a were scratched portions of the processing type T4a, and the processing strength was "weak".

[0211] The film F24a was produced as follows: A laminated film corresponding to the film F14a was produced in the same manner as the film F14a, and then the laminated film was fed in the MD direction, and the scratched portion 30P6 was formed in the intended locations for the steam release portion 31 and the opening induction portion 32 in the same manner as the film F14b.

[0212] <Film F24b> Film F24b had layer structure X4, and was a film in which scratched portion 30P5 was used as steam release processed portion 31, and scratched portion 30P6 was used as opening induction processed portion 32. The steam release processed portion 31 in film F24b was a scratched portion of processing type T4b, and the processing strength was "strong." The opening induction processed portion 32 in film F24b was a scratched portion of processing type T4a, and the processing strength was "weak."

[0213] The film F24b was produced as follows. After producing a laminated film corresponding to the film F14a in the same manner as the film F14a, the laminated film was fed in the MD direction, and the scratched portion 30P6 was formed at the intended location for the opening induction portion 32 in the same manner as the film F14b, and the scratched portion 30P5 was formed at the intended location for the steam release portion 31 in the same manner as the film F14c. As a result, the film F24b was obtained.

[0214] <Film F24c> The film F24c had a layer structure X4, and was a film in which the scratched portion 30P5 was used as the steam release processed portion 31 and the opening induction processed portion 32. The steam release processed portion 31 and the opening induction processed portion 32 in the film F24c were scratched portions of the processing type T5b, and the processing strength was "strong".

[0215] Film F24c was produced by producing a laminated film corresponding to film F14a in the same manner as film F14a, and then, while flowing the laminated film in the MD direction, forming scratch processing portion 30P5 at the intended locations for forming steam release processing portion 31 and opening induction processing portion 32 in the same manner as film F14c.

[0216] (1) Experimental Example 10a The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in experimental example 7a, except that film F24a was used as film F2 constituting the packaging bag 1B shown in Figure 18.

[0217] (2) Experimental Example 10b The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in experimental example 7a, except that film F24b was used as film F2 constituting the packaging bag 1B shown in Figure 18.

[0218] (3) Experimental Example 10c The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in Experimental Example 7a, except that the film F24c was used as the film F2 constituting the packaging bag 1B shown in Figure 18.

[0219] [Experimental Example 11] In Experimental Example 11, films F25a, F25b, and F25c were prepared as the film F2 constituting the packaging bag 1B shown in FIG.

[0220] <Film F25a> The film F25a had a layer structure X5, and was a film in which the scratched portion 30P6 was adopted as the steam release processed portion 31 and the opening induction processed portion 32. The steam release processed portion 31 and the opening induction processed portion 32 in the film F25a were scratched portions of the processing type T5a, and the processing strength was "weak."

[0221] The film F25a was produced as follows: A laminated film corresponding to the film F15a was produced in the same manner as the film F15a, and then the laminated film was fed in the MD direction, and the scratched portion 30P6 was formed in the intended locations for the steam release portion 31 and the opening induction portion 32 in the same manner as the film F15b.

[0222] <Film F25b> Film F25b had layer structure X5, and was a film in which scratched portion 30P5 was used as steam release processed portion 31 and scratched portion 30P6 was used as opening induction processed portion 32. The steam release processed portion 31 in film F25b was a scratched portion of processing type T5b, and had a processing strength of "strong." The opening induction processed portion 32 in film F25b was a scratched portion of processing type T5a, and had a processing strength of "weak."

[0223] The film F25b was produced as follows. After producing a laminated film corresponding to the film F15a in the same manner as the film F15a, the laminated film was fed in the MD direction, and the scratched portion 30P6 was formed at the intended location for the opening induction portion 32 in the same manner as the film F15b, and the scratched portion 30P5 was formed at the intended location for the steam release portion 31 in the same manner as the film F15c. As a result, the film F25b was obtained.

[0224] <Film F25c> The film F25c had a layer structure X5, and was a film in which the scratched portion 30P5 was adopted as the steam release processed portion 31 and the opening induction processed portion 32. The steam release processed portion 31 and the opening induction processed portion 32 in the film F25c were scratched portions of the processing type T5b, and the processing strength was "strong".

[0225] Film F25c was produced in the same manner as film F15a by producing a laminated film corresponding to film F15a, and then, while flowing the laminated film in the MD direction, forming scratch processed portions 30P5 at the intended locations for forming the steam release processed portion 31 and the opening induction processed portion 32, in the same manner as film F15c.

[0226] (1) Experimental Example 11a The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in experimental example 7a, except that film F25a was used as film F2 constituting the packaging bag 1B shown in Figure 18.

[0227] (2) Experimental Example 11b The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in experimental example 7a, except that film F25b was used as film F2 constituting the packaging bag 1B shown in Figure 18.

[0228] (3) Experimental Example 11c The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in experimental example 7a, except that film F25c was used as film F2 constituting the packaging bag 1B shown in Figure 18.

[0229] [Experimental Example 12] In Experimental Example 12, films F26a, F26b, and F26c were prepared as the film F2 constituting the packaging bag 1B shown in FIG.

[0230] <Film F26a> The film F26a had a layer structure X6, and was a film in which the scratched portion 30P6 was adopted as the steam release processed portion 31 and the opening induction processed portion 32. The steam release processed portion 31 and the opening induction processed portion 32 in the film F26a were scratched portions of the processing type T6A, and the processing strength was "weak."

[0231] The film F26a was produced as follows: A laminated film corresponding to the film F16a was produced in the same manner as the film F16a, and then the laminated film was fed in the MD direction, and the scratched portion 30P6 was formed in the intended locations for the steam release portion 31 and the opening induction portion 32 in the same manner as the film F16b.

[0232] <Film F26b> Film F26b had layer structure X6, and was a film in which scratched portion 30P5 was used as steam release processed portion 31 and scratched portion 30P6 was used as opening induction processed portion 32. The steam release processed portion 31 in film F26b was a scratched portion of processing type T6b, and the processing strength was "strong." The opening induction processed portion 32 in film F26b was a scratched portion of processing type T6a, and the processing strength was "weak."

[0233] The film F26b was produced as follows. After producing a laminated film corresponding to the film F16a in the same manner as the film F16a, the laminated film was fed in the MD direction, and the scratched portion 30P6 was formed at the intended location for the opening induction portion 32 in the same manner as the film F16b, and the scratched portion 30P5 was formed at the intended location for the steam release portion 31 in the same manner as the film F16c. As a result, the film F24b was obtained.

[0234] <Film F26c> The film F26c had a layer structure X6, and was a film in which the scratched portion 30P5 was used as the steam release processed portion 31 and the opening induction processed portion 32. The steam release processed portion 31 and the opening induction processed portion 32 in the film F26c were scratched portions of the processing type T6b, and the processing strength was "strong".

[0235] Film F26c was produced by producing a laminated film corresponding to film F16a in the same manner as film F16a, and then, while flowing the laminated film in the MD direction, forming scratch processing portion 30P5 at the intended locations for forming steam release processing portion 31 and opening induction processing portion 32 in the same manner as film F16c.

[0236] (1) Experimental Example 12a The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in experimental example 7a, except that film F26a was used as film F2 constituting the packaging bag 1B shown in Figure 18.

[0237] (2) Experimental Example 12b The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in experimental example 7a, except that film F26b was used as film F2 constituting the packaging bag 1B shown in Figure 18.

[0238] (3) Experimental Example 12c The steam release processed portion 31 and the opening induction processed portion 32 were evaluated in the same manner as in Experimental Example 7a, except that the film F26c was used as the film F2 constituting the packaging bag 1B shown in Figure 18.

[0239] The evaluation results of the steam release processed portion 31 and the opening induction processed portion 32 in Experimental Examples 7 to 12 are shown in Figure 19. As shown in Figure 19, when the steam release processed portion 31 was evaluated as "steam passing" and the opening induction processed portion 32 was evaluated as "no change", the overall evaluation was "A", and otherwise the overall evaluation was "B".

[0240] Based on FIG. 19, when the processing strength of the steam release processed part 31 is "strong" and the processing strength of the opening induction processed part 32 is "weak", the overall evaluation is "A". That is, when the overall evaluation is "A", the evaluation of the steam release processed part 31 is "steam passing", so even if both the steam release processed part 31 and the opening induction processed part 32 are formed on the pillow bag, steam can be selectively released from the steam release processed part 31 during microwave heating. When the overall evaluation is "A", the evaluation of the opening induction processed part 32 is "no change", so the opening induction processed part 32 does not substantially stretch even when heated up in the microwave. In other words, the thermal softening of the resin film caused by heating up in the microwave is suppressed. As a result, the packaging bag 1B can be easily opened using the opening induction processed part 32.

[0241] When the processing strength of the steam release processed part 31 is "strong", the ratio to the unprocessed part is less than 75% as shown in Fig. 16, and when the processing strength of the opening induction processed part 32 is "weak", the ratio to the unprocessed part is 80% or more as shown in Fig. 16. Therefore, it can be seen that by forming the steam release processed part 31 and the opening induction processed part 32 so as to satisfy conditions 1 and 2, it is possible to selectively release steam from the steam release processed part 31 during microwave heating, while easily opening the package by using the opening induction processed part 32 after the package is heated up from the microwave.

[0242] Although an embodiment of the present invention has been described above, the present invention is not limited to the above-described embodiment, but includes the scope indicated by the claims, and is intended to include all modifications within the meaning and scope of the claims.

[0243] The scratch processing part formed by using the sewing machine processing may be formed by laser processing. The scratch processing part formed by the laser processing may be formed by the sewing machine processing. The method of forming the scratch processing part is not limited to the sewing machine processing or the laser processing. [Explanation of symbols]

[0244] 1...packaging bag, 6...storage space, 10...film, 11...sealant layer, 12...outer layer, 30...scratched portion, 30P1...scratched portion (scratched portion penetrating the first resin layer and the second resin layer), 30P2...scratched portion (scratched portion penetrating the second resin layer), 30P3...scratched portion (scratched portion penetrating the first resin layer), 30P4...scratched portion (scratched portion formed from the first resin layer to halfway through the second resin layer), 30P5...scratched portion (scratched portion penetrating the first resin layer). 30P6... scratched portion (scratched portion that does not penetrate the first resin layer) 31... steam release processed portion, 32... opening induction processed portion, 40... test piece, 40a... test piece (reference test piece), 40b... test piece (first test piece or second test piece), 100... contents, 121... first resin layer, 122... second resin layer.

Claims

1. A packaging bag for microwave heating that is sealed to form a storage space for storing contents, a film having a sealant layer and an outer layer laminated to the sealant layer; A steam release portion formed on the outer layer for exhausting steam generated in the storage space by heating; An opening induction processing part formed on the outer layer for assisting opening; Equipped with The steam release processing portion and the opening induction processing portion are formed so as to satisfy condition 1 and condition 2 based on the 5% elongation maximum strength defined below. packaging bag. [Maximum strength at 5% stretching] A rectangular test specimen having a width of 15 mm is prepared, and the test specimen is held in the long side direction of the test specimen by a pair of holding parts. In an environment of 100°C±5°C, the distance between the pair of holding parts is set to 100 mm±2 mm, and the test specimen is pulled in the long side direction at a tensile speed of 200 mm / min. The maximum strength when the test specimen is displaced by 5% or the maximum strength when the test specimen breaks within 5% displacement. (Condition 1) When the test piece has the same layer structure as the film, the direction perpendicular to the long side direction is the MD direction of the film, and the steam release processing portion and the opening induction processing portion are not formed, and when the test piece in which the steam release processing portion is formed along the direction perpendicular to the long side direction at the center of the pair of retaining portions in the long side direction of the reference test piece is called a first test piece, the 5% stretch maximum strength of the first test piece is less than 75% of the 5% stretch maximum strength of the reference test piece. (Condition 2) When the test piece in which the opening induction processing portion is formed along a direction perpendicular to the long side direction at the center of the pair of retaining portions in the long side direction of the reference test piece is referred to as a second test piece, the 5% elongation maximum strength of the second test piece is 80% or more of the 5% elongation maximum strength of the reference test piece.

2. The sealant layer is composed of linear low-density polyethylene. The packaging bag according to claim 1.

3. The maximum internal pressure of the storage space when heated at 500 W for 2 minutes is 0.113 MPa or less; The packaging bag according to claim 1 or 2.

4. A cylindrical portion formed of the film and having a back seal portion; a first seal portion formed at a first end of the tubular portion; a second seal portion formed at a second end of the cylindrical portion opposite to the first end; The packaging bag according to claim 1 .

5. The outer layer is A first resin layer; a second resin layer located between the first resin layer and the sealant layer; having The vapor release processed portion is a scratch processed portion penetrating the first resin layer and the second resin layer, The opening induction processing portion is a scratch processing portion that penetrates one of the first resin layer and the second resin layer, or a scratch processing portion that is formed from the first resin layer to the middle of the second resin layer. The packaging bag according to claim 1.

6. The outer layer is a first resin layer, The vapor release processed portion is a scratch processed portion penetrating the first resin layer, The opening induction processed portion is a scratch processed portion formed in the first resin layer so as not to penetrate the first resin layer. The packaging bag according to claim 1.

Citation Information

Patent Citations

  • Packaging bag and package

    JP2014227222A